The Stringent Response-Regulated sRNA Transcriptome of Borrelia burgdorferi - Drecktrah, Dan; Hall, Laura S.; Rescheneder, Philipp; Lybecker, Meghan; Samuels, D. Scott (Frontiers in Cellular and Infection Microbiology, 2018)
The Lyme disease spirochete Borrelia (Borreliella) burgdorferi must tolerate nutrient stress to persist in the tick phase of its enzootic life cycle. We previously found that the stringent response mediated by RelBbu globally regulates gene expression to facilitate persistence in the tick vector. Here, we show that RelBbu regulates the expression of a swath of small RNAs (sRNA), affecting 36% of previously identified sRNAs in B. burgdorferi. This is the first sRNA regulatory mechanism identified in any spirochete. Threefold more sRNAs were RelBbu-upregulated than downregulated during nutrient stress and included antisense, intergenic and 5′ untranslated region sRNAs. RelBbu-regulated sRNAs associated with genes known to be important for host infection (bosR and dhhp) as well as persistence in the tick (glpF and hk1) were identified, suggesting potential mechanisms for post-transcriptional regulation of gene expression.